2008
DOI: 10.1002/jmv.21181
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of VP4 and VP7 genotypes of human rotavirus in Ecuadorian children with acute diarrhea

Abstract: The objective of the present study was to determine rotavirus etiology and prevalence of the different rotavirus serotypes in Ecuadorian children younger than 5 years of age with gastroenteritis. Children (729) less than 5 years of age with acute diarrhea from either public or private primary health care centers in 10 different provinces of Ecuador, between March 2006 and August 2006 were included in the study. Rotavirus infection was diagnosed using a commercial immunoenzymatic test. Rotavirus isolated from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…A recent study in Ecuador has reported G9 at only 43% among samples collected in 10 clinics during 2006 (Naranjo et al, 2008) and our data show that in 2007, G9 prevalence fell to below 10% (unpublished data). A rapid decline was also recently reported in Thailand, where G9 rotavirus peaked at >90% prevalence in 2001–02, but accounted for less than a third of typed samples in the two following years (Khamrin et al, 2007).…”
Section: Introductionsupporting
confidence: 70%
“…A recent study in Ecuador has reported G9 at only 43% among samples collected in 10 clinics during 2006 (Naranjo et al, 2008) and our data show that in 2007, G9 prevalence fell to below 10% (unpublished data). A rapid decline was also recently reported in Thailand, where G9 rotavirus peaked at >90% prevalence in 2001–02, but accounted for less than a third of typed samples in the two following years (Khamrin et al, 2007).…”
Section: Introductionsupporting
confidence: 70%
“…In a previous publication, data was presented showing that in 2005 G9 was the dominant strain circulating along the coast of Esmeraldas and in the Andean city of Quito [Endara et al, 2007]. This was consistent with another study describing rotavirus in urban settings in Ecuador [Naranjo et al, 2008]. There have been many other studies corroborating the emergence of G9 rotavirus in Latin America [Gentsch et al, 2005;.…”
Section: Discussionsupporting
confidence: 82%
“…Two studies describing the rotavirus genotype distribution were conducted during 2005 in Ecuador [Endara et al, 2007;Naranjo et al, 2008]. Both studies showed that G9 was the most common genotype circulating throughout the country (10 provinces within the coastal, Andian, and Amazonian regions).…”
Section: Introductionmentioning
confidence: 99%
“…This pair of genotypes was detected in 41 out of 61 positive samples, which is quite a surprising result, as no single pair of genotypes has so far been observed to predominate [ 15 – 20 ]. Moreover, both the P9 and G3 genotype are rarely found in other studies: the G3 genotype is only seen in 1% to 5% of cases [ 16 – 18 , 20 ]. Only Ye et al .…”
Section: Discussionmentioning
confidence: 90%